Las citaciones como marca o huella de intertextualidad en las tesis de maestría y doctorado. - Guido Torres Orihuela (2017)
The problema of the investigation was: “The quotations as a mark or sign of intertextuality on the master and doctorate’s degree’s tesis in the universities in the south of Peru”. The objectives were to detect the rate of incompatible implicit intertextuality (intellectual plagiarism) and to determine the forms and formats of quotationn (of Social Sciences). The corpus was made of 18 thesis, 15 from national universities and 3 from private universities. Turnitin anti-plagiarism program was applied to all the thesis, detecting a high porcentaje of implicit intertextuality or intellectual plagiarism. Likewise, the forms of quotation were analyzed, reaching the conclusion that only one thesis uses the APA format, but with limitations regarding omission or ignorance of the norms. The other thesis, use the quotations on the footer line and it is confused many times with the footnotes. Similarly most of the direct quotations do not present quotation marks nor page number.